Pulmonary Function and Circulating Adhesion Molecules in Patients with Diabetes Mellitus - Mary S Boulbou; Konstantinos I Gourgoulianis; Efthymia A Petinaki; Vasilios K Klisiaris; Antonios N Maniatis; Paschalis A Molyvdas (Canadian Respiratory Journal)
BACKGROUND: Lung function in diabetes has been reported in several studies with contradictory results. Diabetes mellitus increases expression of adhesion molecules through hyperglycemia. These molecules play an important role in the pathophysiological dysfunction of the vasculature.